The Effect Of Teaching According To The Robinson Strategy On The Achievement And Retention Of Third-Year Students In The Physics Department (Journal of the College of Basic Education, 2025)
The current research aims to know the effect of teaching according to the Robinson strategy (SQ3R) on achievement and retention among third-year students in the Physics Department. To achieve the research objective, the null hypotheses were formulated and an experiment was conducted that lasted a full semester, which is the first semester. The research community consisted of third-year students in the Physics Department, College of Education at Al-Mustansiriya University for the academic year (2022/2023). The broadcast sample was chosen intentionally and amounted to (63) male and female students. The equivalence between the two research groups was confirmed through the variables (age in months, previous information and intelligence). As far as the research tools are concerned, an achievement test was prepared due to the lack of appropriate tests for the research. (40) test paragraphs were formulated, including (30) objective multiple-choice paragraphs, because they have a high degree of stability and are not affected by the subjectivity of the corrector, provide good coverage of the study material and determine the intended learning outcome to a high degree and (10) essay paragraphs. The content validity was verified and the stability coefficients of the observation form were extracted using the Pearson correlation coefficient equation to confirm the objectivity and stability of the form. After the students finished studying all the material allocated for the first semester, the two research groups were tested with an achievement test. It was repeated after a period of 21 days from the application of the post-achievement test. When analyzing the data, it was found that the experimental group students who studied the material according to the Robinson strategy (SQ3R) outperformed the control group who studied the same material in the usual way in terms of achievement and retention. In light of these results, a set of recommendations and special proposals were developed and used in other educational institutions. It was suggested to conduct subsequent studies to complete the current research.